Injury patterns in U15 rugby players in Ulster schools: A Rugby Injury Surveillance (RISUS) Study. Issue 4 (5th May 2021) - Archbold, Pooler; Rankin, Alan T.; Webb, Michael; Davies, Richard; Nicholas, Richard; Eames, Niall W. A.; Wilson, Roger K.; Vincent, John; McKeever, Dónal; Duddy, Kirsty; Matthews, Mark; Bleakley, Chris
Abstract : Participation in collision sports such as rugby union has inherent risk of injury. The aim of this study was to examine injury patterns and risk factors in adolescent rugby players (U15 years). A prospective injury surveillance study was undertaken involving 26 schools (599 male rugby players, mean age 14.7years). Data were collected over the 2016/17 playing season, with injuries classified by body part and diagnosis. We explored the association between risk factors (demographic/biometric; injury history, protective equipment, training profile, level of play) using cox proportional hazard models with time to injury as the dependent variable. Nearly, 30% of players (178/599) suffered at least one injury. Injury incidence is estimated at 14.7 injuries/1000 match hours. Most injuries occurred in the tackle situation (64.6%, 135/209). Common injury sites were head/face (n = 95, 45.5%), ankle (n = 21, 10.0%), or wrist/hand (n = 15, 7.2%). Concussion (n = 79, 37.8%), wrist/ hand fractures (n = 19, 9.1%), or ankle sprains (n = 16, 7.6%) were the most common diagnoses. Seven concussions (8.9%) resulted in more than 28 days absence from play. A higher risk of injury was associated with: previous concussion (AHR 1.45; 95% CI 1.02 to 2.06), and any previous injury (AHR 1.85; 95% CI 1.23 to 2.78). One in three U15 rugby players sustained an injury over a single playing season. Concussion remains a concern in this age group and should be prioritized in future research.